Severe hypotony and filtering bleb leak after intravitreal injection of ranibizumab - Ilias Georgalas; Dimitris Papaconstantinou; Ioannis Tservakis; Chrysanthi Koutsandrea; Ioannis Ladas (Dove Medical Press, 2008)
Ilias Georgalas, Dimitris Papaconstantinou, Ioannis Tservakis, Chrysanthi Koutsandrea, Ioannis Ladas“G.Gennimatas” Hospital of Athens, NHS, Athens, GreeceAbstract: We report a case of a patient with age-related macular degeneration, who had undergone trabeculectomy nine years earlier, and developed severe hypotony and bleb leak after treatment with intravitreal injections of ranibizumab. Although the incident is rare, in patients with longstanding filtering blebs, who need treatment with antivascular endothelial growth factors, close follow-up may be advocated, since the occurrence of bleb rupture could lead to permanent vision loss.Keywords: trabeculectomy, ranibizumab, age-related macular degeneration